2002
DOI: 10.1073/pnas.172170199
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of the Deinococcus radiodurans proteome by using accurate mass tags

Abstract: Understanding biological systems and the roles of their constituents is facilitated by the ability to make quantitative, sensitive, and comprehensive measurements of how their proteome changes, e.g., in response to environmental perturbations. To this end, we have developed a high-throughput methodology to characterize an organism's dynamic proteome based on the combination of global enzymatic digestion, high-resolution liquid chromatographic separations, and analysis by Fourier transform ion cyclotron resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
343
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 370 publications
(354 citation statements)
references
References 43 publications
9
343
1
1
Order By: Relevance
“…The digested sample was ultacentrifuged and dialyzed overnight with a 500 MW cellulose ester membrane. Additional details on the sample handling are given elsewhere [26].…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…The digested sample was ultacentrifuged and dialyzed overnight with a 500 MW cellulose ester membrane. Additional details on the sample handling are given elsewhere [26].…”
Section: Sample Preparationmentioning
confidence: 99%
“…In order to facilitate the comparison of LC retention times for peptides carried out over a series of capillary LC analyses, we have previously described the use of adjusted retention times or normalized elution times (NET) [26]. In order to determine a NET value for a particular monoisotopic mass (M mi ) obtained during an LC run, the following eq is used:…”
Section: Normalized Elution Timementioning
confidence: 99%
See 1 more Smart Citation
“…The utility of high MMA is particularly beneficial for the aforementioned AMT tag approach developed at our laboratory. In the initial demonstration of this approach [44] with Deinococcus radiodurans, only ϳ70% of peptides identified with SEQUEST scores above 2.0 were validated as AMT tags. An analysis of the conversion of PMT tags to AMT tags shows that almost all PMT tags having a SEQUEST cross correlation (X corr ) scores Ͼ4.0 were converted to AMT tags.…”
Section: Capillary Lc-fticr Analysesmentioning
confidence: 99%
“…particular biological system is to be examined many times (e.g., time course studies following perturbations) [43]. The approach initially involved conventional capillary LC-MS/MS studies to yield identified peptide "potential mass and time tags" (PMT tags) that were subsequently validated as "accurate mass and time tags" (AMT tags) if the predicted peptides' accurate masses were observed using FTICR (in a corresponding sample) at an equivalent elution time [44]. These peptide AMT tags thus serve as confident biomarkers to identify peptides/proteins in subsequent studies, and result in much greater throughput.…”
mentioning
confidence: 99%